The metamorphosis - Kafka, Franz, 1883-1924 (Mumbai : Wilco International, 2024)
"The metamorphosis by Franz Kafka, one of his most celebrated works, delves into the absurdity and challenges of modern life. Gregor Samsa wakes up one morning to find himself transformed into a giant insect. So begins the tale of a surreal experience in which Gregor struggles to adapt his humanity to the change. The book deals with alienation, disillusionment and existentialism; as well as the feelings of inadequacy, isolation and guilt."--Back cover.
"Complete and unabridged."
Keywords: Short stories, Austrian -- Translations into English; Alienation (Social psychology) -- Fiction; Psychological fiction